KEPENTINGAN INDONESIA BEKERJASAMA DENGAN ZOOLOGICAL SOCIETY OF LONDON DALAM PROYEK BERBAK CARBON INITIATIVE - Humaira, Aqilah Maharani; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research explain about Indonesia’s interest to working together with Zoological Society of London (ZSL) in Berbak Carbon Initiative (BCI) project in Berbak National Park. Berbak National Park in Jambi is the largest conservation peat swamp forests area in Southeast Asia and entered as a Ramsar site in 1992. National Parks Berbak saving 45 million tonnes of carbon and absorptive capacity of 70 million tons CO²e. In case of damage, the area will release the greenhouse gas emissions such as carbon dioxide (CO²e) into the air amounted to 34.4 million CO2e within a period of 30 years. BCI project commit to preserve ecosystems in global warming emissions reduction program is embodied in the protection of the National Park Berbak, encourage the conservation of forests and wildlife in it, and the economic empowerment of local communities in accordance scheme REDD + program. The economic potential of the sale of forest carbon emissions in Berbak National Park is estimated at USD 167 278 020, equivalent to 1.51 trillion over 30 years or 50 billion per-year, when it traded through the "Voluntary Market" (voluntary market). Key words: carbon, Zoological Society of London, Berbak, Indonesia